2014
DOI: 10.1016/j.aop.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement universality of two-qubit X-states

Abstract: We demonstrate that for every two-qubit state there is a X-counterpart, i.e., a corresponding two-qubit X-state of same spectrum and entanglement, as measured by concurrence, negativity or relative entropy of entanglement. By parametrizing the set of two-qubit X-states and a family of unitary transformations that preserve the sparse structure of a two-qubit X-state density matrix, we obtain the parametric form of a unitary transformation that converts arbitrary two-qubit states into their X-counterparts. Moreo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 67 publications
(114 reference statements)
1
79
0
Order By: Relevance
“…In the next section, we explore the results of Theorems 1 and 2 to show that, unlike it occurs for two-qubit X states [21,23], it is not generally possible to map an arbitrary 2 × 3 state into a 2 × 3 X state of same negativity and purity by means of a unitary transformation, this time supporting the conjecture in Ref. [21].…”
Section: × 3 X-mems Wrt Spectrummentioning
confidence: 92%
See 3 more Smart Citations
“…In the next section, we explore the results of Theorems 1 and 2 to show that, unlike it occurs for two-qubit X states [21,23], it is not generally possible to map an arbitrary 2 × 3 state into a 2 × 3 X state of same negativity and purity by means of a unitary transformation, this time supporting the conjecture in Ref. [21].…”
Section: × 3 X-mems Wrt Spectrummentioning
confidence: 92%
“…This simple observation reveals the set of 2 × 3 X states to be a "less universal" set than that of 2 × 2 X states, since any 2 × 2 state can be mapped into an X state via an entanglementpreserving unitary transformation; a property that has been recently entitled "entanglement universality of twoqubit X states" [21,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 1465 analysis, a slope estimate of −0.864025, again converging in the direction of log(27/64). (Let us remark, regarding the generalized two-qubit version of the [simpler, lower-dimensional] X-states model [20,30,31], that it has been shown that the slope of a [now, log-log] plot of log (prob(| PT | > 0)) versus log tends to −1/2, as → ∞. )…”
Section: Total Separability Probability Formulasmentioning
confidence: 99%